ARİL KETOMETAKRİLATLARIN SENTEZİ VE KARAKTERİZASYONU - SOYKAN, CENGİZ (Fırat Üniveristesi, 1995)
Tez iki kısımdan meydana gelmiştir. Birinci kısımda -C- grubu ihtiva eden yeni bir monomer olarak kullanılacak olan fenasilmetakrilat, fena3ilklorür ve sodyum metakrilattan elde edildi. Bu amaçla fenasilklorür, benzen ve klorasetilklorür arasındaki bir reaksiyonla elde edildi. Elde edilen monomerin yapısal özellikleri İR, ^-NMR ve 13C-NIİR ile aydınlatıldı. Ayrıca yoğunluk ve rnolar kırma indisi gibi fiziksel özellikler bulundu. İkinci kısımda fenasilmetakrilattın dioksanda Bz2Û2 kullanarak homopolimeri ve stirenle kopolimeri yapıldı. Polirnerlerin yapısı İR, 'h-NMR teknikleri ile aydınlatıldı. Homopoli merin ve kopolimerin yoğunluğu sırasıyla d = 1.100 ve 1.094 gr/cm3 olarak bulundu. Ayrıca polirnerlerin limit viskozite sayıları,, çözünürlük parametreleri ve camsı geçiş sıcaklıkları bulundu.ANAHTAR KELİMELER : Fenasilklorür, Fenasilmetakrilat, Stiren, İR, 'h-NIİR,,3C-NIİR, Yoğunluk, Çözünürlük parametresi. Limit viskozite sayısı, Molar kırılma indisi

Two kinds of vork have been done in this thesis. In the first part, phenacylmethacrylate 0 which will be used as a new monomer containing _C- group was obtained from phenacylcloride and natrium methacrylate. For this reason, phenacylcloride was obtained from the reaction between benzene and ehloraeetylchloride. The structure of monomer wa3 characterized by using 1R, *H-NMRand 13C-NMR techniques. Also, several physical properties of this monomer like density and molar refractive index vere measured. In the second part of the work, the homopolymer of phenacylmethacrylate and the copolymer with sty rene were prepared in 1,4-dioxane by using benzoyl peroxide as initiator. IR and ^H-NMR techniques were used to identify the structure of polymers. The densities of homo and copolymer were found to be 1.100 and 1.094 gr/ml respectively. Also, limit viscosity numbers, solubility parameters and glass transition temperatures of polymers were determined.Key Words : phenacylcloride, Phenacylmethacrylate, Styrene, IR, ^H-NMR,,3C-NMR, Density, Solubility parameter, Limit viscosity, Number glass transition temperature. Molar refractive index.
Keywords: Kimya; Chemistry